An analysis on POME qualities and their management practices: a case study in East Coast Region of Malaysia / Nurul Hidayah Mohd Napiah - Mohd Napiah, Nurul Hidayah (Faculty of Plantation and Agrotechnology, 2018)
During the last century, many researchers have devoted their time to find the way to treat POME through advanced technologies rather than common ponding system. In ponding system, there are two ponds which are anaerobic and aerobic. The effluent from palm oil mill can become the main reason for environmental pollution which can kill the aquatic life if discharged untreated. So, secondary data of POME from four different mills in East Coast region was analyzed to ensure that the treated POME is safe and is beneficial to human and environment based on Environment Quality Act 1974. There are some parameters that the mill must understand and follow such as Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), total nitrogen, suspended solid, ammonical nitrogen and oil and grease. However each mill has their own parameters. The POME could subject to fertilizer, directly released into the river, and used to produce biogas based on the BOD level. The POME can give positive impact to human and ecosystem if manage wisely according to the Department of Environment standards with increasing econmomy of Malaysia and prevent pollution.